Avaliação do padrão de produção de mediadores inflamatórios após modulação da via PI3K/GSK3/mTOR em células mononucleares do sangue periférico de pacientes com esquizofrenia estáveis clinicamente - Vívian Thaise da Silveira Anício (2019)
Introduction: Schizophrenia is a severe and chronic mental disorder that affects about 1% of the population with significant impact in perception, affection and thought. Recently the literature has been increasing the observation of an important alteration of the immune response of schizophrenia as a possible etiophysiopathological factor. Among several mechanisms and signaling pathways related in the production of inflammatory mediators, the phosphatidylinositol 3-kinase (PI3K) / protein kinase B (AKT) / mechanistic target of Rapamycin (mTOR) / glycogen synthase kinase (GSK3) pathway is of particular importance. This cellular pathway occurs in different cell subtypes, including peripheral system mononuclear cells (PBMCs) and is related to several crucial functions to brain growth, development and functioning, which are factors compromised in schizophrenia. Objective: To test the hypothesis that there is a deregulation of the PI3K/AKT/GSK3/mTOR signaling pathway in PBMC from clinically stable patients with schizophrenia, which could be related to a possible differential pattern of release of the inflammatory mediators IL- 10, MCP-1, IL-1β, IL-17A, TNF-α and IL-6. Methods: In a cross-sectional study, 11 patients of the Instituto Raul Soares with a diagnosis of schizophrenia (F20.0), clinically stable, and 11 healthy controls from the community, matched 1: 1 according to sex, age and schooling, were recruited for the study. Cytokine levels of plasma and PBMC supernatants, which were incubated with inhibitors of the PI3K, GSK3 and mTOR enzymes, treated or not with the inflammatory stimulus PHA, were quantified by ELISA and CBA. Results: Similar concentration of PBMC (1x107 cells/mL), cells from patients with schizophrenia produce a lower significant amount of baseline IL-10 as compared to controls (p = 0.014). No significant difference was found between baseline levels of the cytokines MCP-1, IL-1β, IL-17A, TNF-α, and IL- 6 produced by PBMC from controls compared to those produced by patients with schizophrenia in the same experimental condition. We also observed that the nonselective PI3K inhibitor (LY294002, 1 or 10 μM), the PI3Kγ selective inhibitor (AS605240, 0.1 or 1 μM), the GSK3β inhibitor (CHIR99021, 1 or 3 μM) and the mTOR inhibitor (rapamycin, 0,5 or 2.5 nM) did not alter IL-10, IL-β, IL-17A, IL-17A, TNF-α and IL-6 levels produced by PBMC from controls and from patients with schizophrenia treated or not with PHA. In addition, the GSK3β inhibitor (CHIR99021, 1 or 3 μM) did not alter the levels of MCP-1 produced by PBMC from controls and from patients with schizophrenia, treated or not with PHA. On the other hand, the non-selective inhibitor of PI3K (LY294002, 1 or 10 μM) and the mTOR inhibitor (rapamycin, 0.5 or 2.5 nM) were able to decrease the levels of MCP-1 produced by PBMC obtained from controls and of patients with schizophrenia, treated or not with PHA. Regarding plasma levels, we did not find significant differences in the concentration of IL-6, IL-10, TNF-α, MCP-1, IL-1β and IL-17A in patients with schizophrenia compared to healthy controls. Conclusion: The similar results between stable patients and controls could be due to the possible stabilization of the PI3K/AKT/GSK3/mTOR by the use of neuropsychiatric drugs. However, the reduced basal IL-10 levels observed in patients indicate new possibilities and insights about the future molecular modulation of this disease.